PSYCHOLOGICAL CHARACTERISTICS OF BULLYING MANIFESTATIONS IN YOUNG SCHOOL-AGED CHILDREN (Innovate Conferences, 2025)
This research paper investigates the psychological characteristics associated with bullying behavior in primary school-aged children, focusing on personality traits, emotional regulation, and peer group dynamics. Conducted across four public schools, the study involved 103 children aged 6 to 11, alongside input from 14 teachers and 4 psychologists. The research categorizes children into psychological profiles—dominant-aggressive, anxious-withdrawn, adaptive-neutral—and analyzes the internal and external factors that trigger bullying. Findings reveal that poor impulse control, social insecurity, and low empathy are strong predictors of both aggression and victimization. Recommendations emphasize early psychological diagnostics, inclusive group tasks, and peer mediation.